[Teaching, Learning and Researching Experiences] - Kidney, James (1999)
Keywords: dept.mgt; faculty_collection; sabbatical_report

Integration of Computer Usage in Management and Law Courses. - Prasad, Durga (1993)
Keywords: dept.mgt; faculty_collection; sabbatical_report

Daily Business Etiquette. - Frank, Ellen (1992)
Keywords: dept.mgt; faculty_collection; sabbatical_report

Managerial resistance to change: Romania’s quest for a market economy - Catana, D.; Catana, A.; Finlay, J.L. (Journal of East European Management Studies, 1999)
This exploratory investigation relates traditional theories on resistance to change to privatization of the Romanian economy. The authors identified several “inhibitors” which have served to stall Romania’s attempts to achieve a free-market economy. While a lack of practical training in western-style management practices may be a limiting factor, Romanian managers are generally open to change. However, they are still deeply rooted in the thought processes instilled during Romania’s command economy and a belief that the size and economic importance of their firms will serve as buffers against the “agents of change”. To the extent that change is viewed as a threat to their personal interests, resistance can be expected. The question, “what is in it for me?”, must be satisfactorily addressed if Romanian managers are expected to become active partners in implementing necessary changes. © 1999, Nomos Verlagsgesellschaft mbH und Co. All rights reserved.
Keywords: dept.mgt

Business students' perceptions of women in management - Frank, Ellen J (Sex Roles, 1988)
This study surveyed 202 undergraduate business majors regarding their perceptions of women in management. Research focused on male and female students' acceptance of women managers, the extent students perceived women managers as being accepted by others, and a comparison of descriptions of the typical male and female manager. Male students were found to be less accepting of women's dual role. Men perceived women managers as being less knowledgeable and possessing poorer managerial skills than male managers. Women managers were perceived as having greater interpersonal skills. Female students showed a greater preference for a male boss. Their descriptions of women managers were more positive regarding competency, but emphasized an interpersonal rather than a task orientation. The conclusion is made that perceptual stereotypes have not radically changed when compared to research reported in the 1970s. © 1988 Plenum Publishing Corporation.
Keywords: dept.mgt

Designing and implementing a personnel mis - Frank, EJ (Personnel, 1987)
Keywords: dept.mgt; ⛔ No DOI found

Noren discount stores: death of a family business - Goldberg, Steven D (Family Business Review, 1997)
This case is about a family-owned discount store chain that was unable to survive much beyond its founder. It tells the story of a first-generation American family and its struggle to grow and prosper in a family business during the early 1900s. The case takes the reader through the business' growth, maturity, decline, and, ultimately, its demise in 1991, which was brought about by issues such as organizational structure, the role of family in the family business, lack of succession planning, and myopic strategic planning. The author uses fictitious names, dates, and places to protect the surviving family members' privacy, and to ensure confidentiality.
Keywords: dept.mgt

Organizational cynicism - Dean, James W.; Brandes, Pamela; Dharwadkar, Ravi (Academy of Management Review, 1998)
Keywords: dept.mgt

Give your work teams time and training - Cottrill, Melville (Academy of Management Perspectives, 1997)
Keywords: dept.mgt

Predicting corporate social responsiveness: A model drawn from three perspectives - Beliveau, Barbara; Cottrill, Melville; O'Neill, Hugh M. (Journal of Business Ethics, 1994)
Most studies of corporate social responsiveness (CSR) focus on the relationship between CSR and profit. Here, we use three perspectives (institutional theory, economic theory and agency theory) to explain CSR. Industry norms, market share and indicators of management reputation predict variance in CSR. The combined perspectives improve understanding of both CSR and the CSR-profit relationship in two ways. First, they suggest that CSR levels and their relationship with profit will vary by industry. Second, they suggest that stock market measures and accounting measures will respond differently to CSR measures. Stock market measures lead, while accounting measures lag, CSR.
Keywords: Agency Theory; Economic Growth; Economic Theory; Market Share; Stock Market; dept.mgt

Using simulations to investigate management decision making - Prohaska, Charles R; Frank, Ellen J (Simulation & Gaming, 1990)
Management researchers are always in search for new controlled environments from which they can gather data. This article proposes the use of total enterprise simulations as a research setting for studying management decision making. Using INTOP, the authors present examples of analyses that were conducted from a data base generated from the responses of executive MBA participants. Using a multiple regression, policy-capture approach, differences in the decision making strategies between groups are examined. Also discussed is an approach to developing a performance criterion that may be used when testing hypotheses regarding managerial decision-making effectiveness. The authorsconclude that total enterprise simulations represent a research setting that warrants further exploration. © 1990, SAGE Publications. All rights reserved.
Keywords: decision making; dept.mgt; management performance; policy capture; research methodology; simulation